2016
DOI: 10.1017/s0144686x16000982
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and unproductive? Stereotypes of older employees in corporate and news media

Abstract: Older employees face a severe employability problem, partly because of dominant stereotypes about them. This study investigates stereotypes of older employees in corporate and news media. Drawing on the Stereotype Content Model, we content analysed newspaper coverage and corporate media of 50 large-scale Dutch organisations, published between 2006 and 2013. The data revealed that stereotypical portrayals of older employees are more common in news media than in corporate media and mixed in terms of valence. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 52 publications
1
32
0
2
Order By: Relevance
“…Arguably this stereotype about the ambitions of older workers could limit the opportunities for those older workers who wanted to progress. As previous research has found, opportunities for older workers to develop and progress may be limited (Beck, 2014; Kroon et al ., 2018). Another manager commented that they tended to promote younger workers: I think the older they get out there, when you say you're doing a good job, I'm thinking of promoting you, they're quite happy doing what they're doing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably this stereotype about the ambitions of older workers could limit the opportunities for those older workers who wanted to progress. As previous research has found, opportunities for older workers to develop and progress may be limited (Beck, 2014; Kroon et al ., 2018). Another manager commented that they tended to promote younger workers: I think the older they get out there, when you say you're doing a good job, I'm thinking of promoting you, they're quite happy doing what they're doing.…”
Section: Resultsmentioning
confidence: 99%
“…Positive stereotypes about older workers can also perversely create barriers for older workers. For example, perceptions regarding the mentoring role of older workers may limit the (training and development) opportunities available to them (Kroon et al ., 2018). There may also be expectations that older workers take on additional roles in order to make available learning opportunities to younger colleagues (Beck, 2014).…”
Section: Age Management In the Workplacementioning
confidence: 99%
“…The negative role of social stereotypes is also noted by foreign researchers. For example, Dutch scientists [25] believe that negative stereotypical images of older employees are more common in the media than in corporate ones.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%
“…The current study considers the influence of both the visibility of older workers in the news, and media stereotypes about older workers. Common negative stereotypes that are present in Dutch news media relate to older workers’ poor health and low productivity, while positive media stereotypes relate to older workers knowledge, experience, and reliability (Kroon et al 2016b ). In the current study, discrimination claims are traced among older workers aged 45 years and older, as from this age limit on it becomes increasingly difficult for individuals to reenter the labor market after job loss in the Netherlands (Bierings and Loog 2013 ).…”
Section: Age Discrimination and News Coveragementioning
confidence: 99%
“…A long-standing history of research has consistently demonstrated that media portrayals of diverse groups in society can be biased and have the potential to promote the reliance on stereotypes when making decisions regarding, for example, whom to hire or fire (e.g., Ramasubramanian 2011 ; Ramasubramanian and Oliver, 2007 ). In the specific case of older workers, previous research finds that news media portray this group in terms of dominant stereotypes (Kroon et al 2016b ) and that exposure to such media stereotypes leads to a bias in perceptions and selection of older workers (Kroon et al 2016a ).…”
Section: Introductionmentioning
confidence: 99%